2005
DOI: 10.1007/s00464-004-2165-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open appendectomy in acute appendicitis: A randomized prospective study

Abstract: We believe that LA is effective in any kind of clinical situation, with low traumatic impact and best comfort for the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 14 publications
4
40
1
4
Order By: Relevance
“…However, several randomized controlled trials comparing laparoscopic with open appendectomy have provided conflicting results [9,10]. Previous studies have demonstrated better clinical short-term outcomes with the laparoscopic approach [11][12][13], while other studies have shown marginal or no short-term clinical benefits [14][15][16]. Bearing in mind that laparoscopic appendectomy, unlike other laparoscopic procedures, has not been found superior to open surgery for acute appendicitis [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, several randomized controlled trials comparing laparoscopic with open appendectomy have provided conflicting results [9,10]. Previous studies have demonstrated better clinical short-term outcomes with the laparoscopic approach [11][12][13], while other studies have shown marginal or no short-term clinical benefits [14][15][16]. Bearing in mind that laparoscopic appendectomy, unlike other laparoscopic procedures, has not been found superior to open surgery for acute appendicitis [17].…”
Section: Introductionmentioning
confidence: 99%
“…Many authors foresees Laparoscopic surgery as a reliable future tool for intraabdominal surgical pathologies in order to provide less invasiveness with maximum comfort and outcomes 6,7 . Several studies [8][9][10][11][12][13][14][15] have shown that laparoscopic appendectomy is safe with faster recovery and least wound complication.…”
Section: Discussionmentioning
confidence: 99%
“…But still no superiority to the open classic technique was demonstrated in the literatures comparing LA and classic appendectomy. [9][10][11][12][13] Besides these benefits in laparoscopy there are some dis-advantages and limitations of it such as; the long operation times for performing a laparoscopic surgery, complications of the laparoscopic techniques and the higher costs of the laparoscopic surgery due to the devices used. [14,15] For these reasons the laparoscopic technique is not accepted as the gold-standard approach in acute appendicitis.…”
Section: Discussionmentioning
confidence: 99%